Large posterior mediastinal goiter post total cervical thyroidectomy: a case report - Fesatidou, Maria; Fesatidou, Vasiliki; Tsoulfas, Georgios; Fessatidis, Ioannis T. (International Surgery Journal, 2020)
Thoracotomy approach is indicated for a complete and safe posterior mediastinal goitre removal. A 68 years old male was hospitalized due to a right mediastinal mass found in a chest X-ray and confirmed by computed tomography. The patient had undergone total cervical thyroidectomy thirty years ago. A computed tomography (CT) guided percutaneous needle biopsy of the mass revealed thyroid tissue. Subsequently, the mass was completely resected through a right posterolateral thoracotomy. The histopathology confirmed a large mediastinal goitre with no signs of malignancy. The patient had an uncomplicated recovery. We present a relatively rare case of a successful resection of a posterior mediastinal goitre, occurring thirty years post-total cervical thyroidectomy. We advocate lateral thoracotomy to achieve a broad operative field and enhance surgical safety.